Study on the Use of Biopolymer from Wood Extraction as an Additive in Gold Cyanidation Process to Improve Gold Recovery at Antam Pongkor Gold Mine - (NIM : 22109303), CHANDRA
Development in cyanidation leaching of gold ore, particularly in plant operations, essentially aim at two main objectives, namely to increase gold and silver recoveries and plant throughput. Various research works has been focusing on the optimization of reagents addition (cyanide, oxygen, lead nitrate), improving measurement and control of these parameters, as well as adoption of new equipments and automatization methods. Lead nitrate has been commonly used in gold cyanidation plant as an additive to increase gold recovery during leaching. This research was focused on the use a new additive of a lignin-based biopolymer which is extracted from wood extraction for improving recoveries of gold and silver. This biopolymer has been used in various applications such as in oil drilling, cement and concrete industry due to its several properties such as viscosity modifier, dispersant, depressant, and binder. However, the application of this biopolymer in gold cyanidation process is new and never been applied commercially in any gold mine worlwide. Series of cyanidation tesworks with and without the additions of biopolymer have been conducted at laboratory and plant scale at PT Antam's Gold Mine and Processing Plant in Pongkor. For the laboratory-scale experiments, samples were taken from the plant feed and were prepared to obtain batches of sample which were homogeneous. The size distribution of the prepared sample resembled the actual condition in the plant (i.e at least 80% <74μm). Laboratory experiments was carried out to measure the changes in viscosity of the slurry by the addition biopolymer; to get a statistically convincing result that biopolymers can improve gold recovery by replicate the pre-test up to five times to compare the gold recoveries under conditions with and without addition of the biopolymer during cyanidation; to investigate the effects of the biopolymer concentration on gold variations of cyanide concentration, solid to slurry ratio (%solid), and particle size distribution of the ore on the gold and silver recoveries. The plant-scale experiment was conducted in the CIL circuit of plant I. The method was to collect data in two periods; each period was carried out for two weeks in the presence and absences of the biopolymer in the cyanidation process. The plant trial results were compared with those of laboratory scale results, especially in term of the effect of the biopolymer addition on the increase of gold recovery. Repeated test results, consistently shows that the additions of biopolymer resulted in the increase of gold and silver recoveries. The increase in gold and silver recovery depends on the concentration of biopolymers in the slurry, in which increasing the concentration of the biopolymers in the slurry increased the recovery until certain level of the biopolymer dosage. The highest of gold recovery at laboratory leaching tests was obtained at the biopolymer concentration of 800 ppm. Under this condition, the increase of gold and silver recoveries was respectively 4.5% and 6.4%. The use of biopolymers in cyanidation also enhanced the rate of gold dissolution. The use of the biopolymer in cyanidation can cover the decline of gold recovery due to the increase of solid percentage, thus providing the opportunitye to increase the throughtput of the plant by increasing solid percentage of the slurry and also reducing the reagents consumption per tonne of ore at the leaching stage. The results of plant trial exhibits also similar tendency with the results of laboratory test in means that the addition of the biopolymer in the leach tank increased the gold and silver recoveries. The increase of gold and silver recoveries in plant trial are dependent on the feed head grade, in which at 6 g/t of gold head grade, the gold recovery increases up to 3%. It can be concluded that the biopolymer can improve the gold recovery in two ways. Firstly, the biopolymer cause the fine particles stay dispersed evenly in the slurry and hindered coagulation, so that all surface of the fine particles got the same chance to contact with cyanide and oxygen in the slurry. Secondly, the biopolymer enhances the dissolution of pyrite as indicated by a lower cyanide concentration, lower pH and higher iron content in the tailing slurry. Beside of the positive impact on improving the recovery, the use of biopolymers as an additive also had negative impacts that should be anticipated, mostly is a tendency of the coarser particles settling in the presence of this additive during leaching.